(1652) Towards Developing an Assessment Metric for E-services: a case study Egypt نحو تطوير معيار تقييم للخدمات الإلكترونية: دراسة حالة مصر - Nosseir, Ann (معهد التخطيط القومى, 2022)
Since the mid 1980s, Egypt has realized significant growth in information and communication technology usage across different sectors in the economy. in order to generate economic development and growth.